Adaptation strategies for coral reef ecosystems in Small Island Developing States: Integrated modelling of local pressures and long-term climate changes. (20th April 2020) - Hafezi, M.; Sahin, O.; Stewart, R.A.; Connolly, R.M.; Mackey, B.; Ware, D.
Abstract: Planning and decision-making vastly benefit from a holistic and systematic understanding of the long-term impacts of climate change and other non-climatic stressors on the health and resilience of coral reef ecosystems, and the efficacy of adaptation strategies and management interventions on mitigating these impacts and maintaining ecosystem condition and associated ecosystem service. This study reports on an approach to modelling coral reef stressors and possible adaptation interventions using the coral reef ecosystem of Port Resolution on Tanna Island, Vanuatu as the case study serving as a microcosm of endangered Pacific Small Island Developing States (SIDS). A novel participatory modelling framework was developed and followed in a stepwise manner to integrate local and long-term climate change pressures by coupling structural analysis and the Bayesian Network (BN) techniques. The BN model was quantified through an advanced consolidated data-induced, evidence-based, and expert-driven approach that incorporated: (1) projections of future climate conditions and changing human activities; (2) the influences of multiple stressors including physical environmental and sociological factors; and (3) spatial variability in the key processes and variables. The first and second phases conceptualised the whole system by providing a graphical presentation of system variables within the Driver-Pressure-State-Impact (DPSI) framework using the structural analysis technique. In the third phase, the BN technique was used to integrate the outcomes of multidisciplinary assessments and analysis with experts' opinion. The BN modelling phase was completed based on evidence extracted from literature which reported the results of regional and downscaled climate models, GIS-based analysis, parametrised data obtained from the region, and tacit knowledge elicited from experts. The validated model was employed to anticipate the future health and resilience condition of coral reefs under different sets of climatic trajectories and adaptive responses scenarios. The results predict the risks to the health and resilience of the Port Resolution coral reef system from the adverse impacts of climate change and harmful human activities and the possible success of adaptations strategies. A sobering conclusion was that despite the current satisfactory condition of coral reefs in the case study zone, their health and resilience would be severely threatened by 2070 in the absence of implementing adaptation strategies and associated sustainable management interventions. Highlights: Using an integrative approach rises the chance of successful execution of adaptation plans. Planning for reefs requires integrated modelling of local pressures and long-term climate changes. Bayesian Network was used to integrate multidisciplinary assessments with experts' opinion. The reefs' resilience would be threatened severely by 2070 in the absence of adaptation strategies.